Exploring the Financial Drivers of Peer-to-Peer Lending Usage: Evidence from the Indonesian Fintech Landscape - Rolando, Benediktus (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Despite Indonesia's rapid digital transformation and significant unbanked population of 51%, the adoption of peer-to-peer (P2P) lending platforms remains below its potential, with cybersecurity incidents and trust issues hindering widespread acceptance. This study investigates the determinants of P2P lending adoption intention in Indonesia by examining the influence of digital literacy, financial literacy, platform trust, security perception, and innovation features. While previous research has explored these factors independently, this study uniquely integrates them into a comprehensive framework within the Indonesian context, where P2P lending has grown to IDR 411.5 trillion in 2023 yet faces persistent adoption challenges. Using a quantitative approach, data was collected from 100 respondents through a structured questionnaire and analysed using multiple statistical methods including validity, reliability, normality, heteroscedasticity, and multiple regression analyses. The results reveal significant positive influences of all five factors on P2P lending adoption intention, with security perception demonstrating the strongest impact (t = 97.543, p < 0.001), followed by platform trust (t = 96.234, p < 0.001). The model explains 78.7% of the variance in adoption intention (R² = 0.787), with all variables showing significant influence both individually and collectively (F = 12.876, p < 0.001). These findings provide crucial insights for platform developers, policy makers, and financial institutions in developing strategies to enhance P2P lending adoption in emerging markets. The study contributes to both theory and practice by offering a validated framework for understanding P2P lending adoption in developing economies while highlighting the critical role of security and trust in digital financial services adoption.